Research Status and Hotspots of Anticancer Natural Products Based on the Patent Literature and Scientific Articles - Shen, Junkai; Li, Jiahuan; Yu, Peiming; Du, Gangjun (Frontiers in Pharmacology, 2022)
Background: Patent literature contains a large amount of information on the internal state of current industrial technologies that is not available in other literature. Scientific papers are the direct embodiment of the achievements of theoretical research in this field and canreveal how current theories in basic research have developed. In this paper, the analysis of both patent literature and scientific papers on natural anticancer products was used to examine the development and status of this field and explore the research hotspots. Methods: Patent data came from the incoPat Patent Retrieval database, and paper data were retrieved from the Web of Science core set and PubMed. GraphPad Prism 8, Microsoft Excel 2010 and CiteSpace 5.8.R3 were used, and visual processing was performed. The patent literature information analyzed includes patent applicant type, country (or region) and technical subject. The analysis of scientific papers includes academic groups, subject areas, keyword clustering and burst detection. Results: At present, antitumor drugs derived from natural products mainly include (1) apoptosis inducers such as curcumin, gallic acid, resveratrol, Theranekron D6 and gallillardin and other compounds; (2) topoisomerase inhibitors such as camptothecins, scaffold-hopped flavones, podophyllotoxin, oxocrebanine and evodiamine derivatives; (3) telomerase inhibitors including camptothecin and isoquinoline alkaloids of Chelidonium majus, amentoflavone and emodin;(4) microtubule inhibitors such as Kolaflavanone, tanshinone IIA analog, eugenol and milelpachine; (5) immunomodulators such as fucoidan, myricetin, bergapten and atractylenolide I;(6) tumor microenvironment regulators such as beta-escin and icaritin; (7) multidrug resistance reversal agents such as berberine, quercetin and dihydromyricetin; and (8) antiangiogenic and antimetastatic agents such as epigallocatechin-3-gallate, lupeol, ononin and saikosaponin A. Conclusion: The development of medicinal plants and the research on the anticancer mechanism of natural active products are still the current research hotspots, especially topics related to immune checkpoints, essential oils and metastatic cancer should be paid close attention. Theories in traditional Chinese medicine such as "Restraining Excessiveness to Acquire Harmony", "Same Treatment for Different Diseases", "Meridian Induction Theory" and "Quxie Fuzheng" have been important in guiding the research of anticancer mechanisms and the development of new drugs and can provide new ideas for this process.